Middle Triassic tetrapod tracks from the Cerro de las Cabras Formation: body mass estimations and paleocommunity reconstruction - Arcaria, M. Rocío; Krapovickas, Verónica; Marsicano, Claudia A.; Mancuso, Adriana C. (Historical Biology, 2025)
The Middle Triassic deposits of Argentina are notable for abundant tetrapod footprints but scarce body fossils. We studied one of the richest Middle Triassic ichnoassociations, the Cerro de las Cabras Formation (Cuyana Basin), generating 3D models and estimating track-makers’ body mass. Size variation among tracks was interpreted as either ontogenetic differences within species (minimum diversity) or taxonomic variation among multiple species (maximum diversity). Track-makers include non-mammalian therapsids (dicynodonts and cynodonts), pseudosuchian archosaurs, and lepidosauromorphs. Dicynodonts are represented by Pentasauropus argentinae with three body mass sizes (3000 kg, 1000 kg and ≈ 250 kg), suggesting 1–3 producers. Four cynodont ichnotaxa (Dicynodontipus isp. Morphotype 1 and 2, cf. Ameghinichnus isp. and Calibarichnus ayestarani) were identified with three body mass ranges (≤2 kg, 2–6 kg and 6–10 kg), indicating 4–8 producers. Four pseudosuchian archosaurs ichnotaxa (Chirotherium barthii, Isochirotherium isp. Chirotherium isp. and Rigalites ischigualastianus) with three body mass ranges (400–900 kg, 1300–1900 kg, and ≈ 7 tons), suggest the presence of 4–7 producers. Lepidosauromorphs tracks (cf. Rhynchosauroides isp.) are represented by one body mass size (≈3 kg). The interpreted tetrapod community resembles others from the Middle-Late Triassic from South America and is consistent with the scarce bone record from Cerro de Las Cabras Formation.
CRIS-Team Scopus Importer:2025-05-30
Keywords: Cuyana Basin; Paleoecology; Tetrapod ichnology; Triassic